Fase inicial de una revisión sistemática de literatura sobre el uso de puntos de carbono en radioterapia (2020)
The properties that only materials with manometric dimensions exhibit are the basis for the development or improvement of different biomedical applications, such as radiotherapy. Nanomaterials offer the possibility of making this form of treatment more efficient by increasing radiosensitivity. Carbon dots are nanoparticles that possess physical, optical and chemical properties that make them attractive to be implemented in radiotherapy. However, as a newly discovered nanomaterial, there are many fields of biomedical research, such as radiotherapy, in which its potential use should be studied. This research practice document consists of the initial phase of a systematic literature review on the use of these carbon-based nanoparticles in radiotherapy. The methodology followed to identify the most relevant literature related to the topic is described, classified according to the main characteristics of the nanomaterial synthesis and the current trend of publications related to the target topic is detailed. It is important to mention that, as this is the initial phase of a research project, it has not been completed and work is still ongoing.